Faktor Sanitasi Lingkungan Dengan Kejadian Diare Pada Balita Di Desa Padang Bindu Kabupaten Muara Enim Tahun 2025 - Welli, Darma; Yustati, Eva; Meliyanti, Fera (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Introduction. Diarrhea in toddlers, if left untreated, can lead to dehydration and death. One risk factor for diarrhea is environmental factors or basic sanitation, including clean water facilities, healthy latrines, and sanitation facilities. Methods. This study used a cross-sectional design. The population in this study was 102 mothers of toddlers aged 1-5 years living in Padang Bindu Village, Muara Enim Regency, with a sample size of 80 toddlers in 2025. Results Univariate analysis showed that of the 80 respondents, 45 (56.3%) toddlers who suffered from diarrhea did not suffer from diarrhea (35 (43.8%), 46 (57.5%) had clean water facilities available, 34 (42.5%), 42 (52.5%), and the availability of family latrines that did not meet the requirements (38 (47.5%). 47 (58.8%) had wastewater disposal facilities that did not meet the requirements (33 (41.3%). Bivariate analysis Chi-square statistical test The availability of clean water facilities, latrines, and SPAL obtained a p-value of 0.000, indicating a significant relationship between clean water facilities, latrines, SPAL, and the incidence of diarrhea in toddlers. Conclusion. There is a significant relationship between clean water facilities (SPAL) and the incidence of diarrhea in toddlers in Padang Bindu Village, Muara Enim Regency in 2025.